Über Sharen von Hyperflächen im Raum korrelativer Elemente - Grincevičius, K. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. И. Гринцявичюс. О семействах гиперповерхностей в пространстве коррелятивных элементовK. Grincevičius. Apie hiperpaviršių šeimą koreliatyvinių elementų erdvėje